Body Contouring Surgical Procedures and New Technologies - Aguilera, Alexandro (IntechOpen, 2023)
Body contouring surgery has evolved in the last few decades, influenced by three main aspects: cultural changes alongside social media and new concepts of beauty, the surgeon and their focus on achieving natural results, and the influence of new technology and devices. This book provides a comprehensive overview of body contouring techniques, including both surgical and nonsurgical procedures. Chapters discuss liposuction of the abdomen and buttocks, ultrasonic devices and internal radiofrequency devices for fat removal, breast implants and lifts, and more.